MANAJEMEN MUTU MADRASAH BERBASIS KEARIFAN LOKAL DALAM PERSPEKTIF JOSEP M. JURAN - Kamila Ida Suwarno (JUMPA : Jurnal Manajemen Pendidikan, 2020)
The quality of a product is one of the most important factors in increasing the competitiveness of a product. Total Quality Management is an approach used in running a business to maximize the competitiveness of an organization through continuous improvement of its services, products, processes and environment. Total Quality Management according to Josep M. Juran Quality is the suitability of a product use (Fitness For Use) which is to meet customer needs and satisfaction. Josep is often referred to as "the Father of Quality" by using the concept of the Quality Trilogy thinking, namely Quality Planning, Quality Control and Quality Improvement. Integrated quality management (Total Quality Management) has success in the business world and impacted on other organizations including educational institutions to implement it. But there is still much debate about TQM applied in management education. Total Quality Management (TQM) needs to be done in every activity of the organization, so that the goals of the organization can be achieved and the investments made have not been in vain. With TQM, it can also be used to assess the ability of existing human resources (HR) to plan human resource improvements and organizational strategies in the future.